2007
DOI: 10.1111/j.1462-5822.2007.01077.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron and fungal pathogenesis: a case study with Cryptococcus neoformans

Abstract: SummaryThe acquisition of iron from mammalian hosts is an important aspect of infection because microbes must compete with the host for this nutrient and iron perception often regulates virulence factor expression. For example, iron levels are known to influence the elaboration of two major virulence factors, the polysaccharide capsule and melanin, in the pathogenic fungus Cryptococcus neoformans. This pathogen, which causes meningoencephalitis in immunocompromised people, acquires iron through the use of secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
108
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(113 citation statements)
references
References 57 publications
(117 reference statements)
3
108
1
1
Order By: Relevance
“…Several recent studies have shown that fungal nutrient and element acquisition pathways may be critical for pathogenicity of both plant and human pathogens [40,41]. For example, all living organisms utilize Cu as cofactor of enzymes functioning in many cellular biochemical processes [3].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have shown that fungal nutrient and element acquisition pathways may be critical for pathogenicity of both plant and human pathogens [40,41]. For example, all living organisms utilize Cu as cofactor of enzymes functioning in many cellular biochemical processes [3].…”
Section: Discussionmentioning
confidence: 99%
“…Iron availability influences at least two major virulence traits in this fungus, including the production of a polysaccharide capsule and deposition of melanin in the cell wall (2,3,4,5,6). Additionally, iron overload exacerbates cryptococcal disease in a mouse model of cryptococcosis (7).…”
mentioning
confidence: 99%
“…neoformans has multiple acquisition mechanisms to obtain iron, including a high-affinity uptake system composed of the iron permease Cft1 and the ferroxidase Cfo1, a siderophore uptake pathway, cell surface reductases, and exported reductants such as 3-hydroxyanthranilic acid; in addition, melanin in the cell wall may contribute to ferric iron reduction (3,8,9). The Cft1/Cfo1 permease/ferroxidase complex is essential for reductive iron uptake, for iron acquisition from transferrin, and for full virulence in a mouse model of cryptococcosis (10,11).…”
mentioning
confidence: 99%
“…One of the principal Rim101-dependent responses to alkaline conditions involves adaptation to iron starvation. Tolerance of iron deprivation at physiological pH is one of the most important virulence determinants of fungi, as freely available iron is strongly limited in human hosts, protecting the host against microorganisms unable to increase iron uptake (7,52,68,(74)(75)(76)(77)(78). Transcriptional analyses have identified several genes involved in iron metabolism and transport, including some Rim101-dependent targets, such as the siderophore iron transporter genes ARN1 and FET3 and the ferric reductase and ion permease genes ENA1, RBT2, FRE2, FRE5, FRE8, FRP1, FRP2, CTR1, and ZRT1 (52,74,79).…”
Section: Pacc/rim101 Effectors and Downstream Targets Involved In Patmentioning
confidence: 99%